'Negotiated planning': Diverse trajectories of implementation in Nairobi, Addis Ababa, and Harare. (January 2017) - Cirolia, Liza Rose; Berrisford, Stephen
Abstract: This paper unpacks how plans are implemented in three African cities: Nairobi, Addis Ababa, and Harare. Three planning implementation instruments form the basis of the comparison across cities. These instruments aim to give effect to plans and include development regulation, infrastructure investment, and land allocation. In contrast to reading African planning efforts as a catalogue of failures, this analysis allows us to see the many actors and complex alliances and dissonances which play out through implementation. Here we propose the concept of 'negotiated planning' as a useful conceptual tool. We argue that the concept is useful for: its departure from normative assumptions about good or proper planning; unpacking the everyday nature of implementation; grounding and contextualising practices; and depathologizing the African city. Highlights: Urban planning studies should pay more attention to the instruments of plan implementation. The concept of 'negotiated planning' explains the contested, power-laden and multi-actor nature of planning implementation. Nairobi, Addis Ababa, and Harare offer unique cases of negotiated planning.